Analisis Kinerja Keuangan Pt Astra International Tbk Pada Periode 2021-2025 - Sulistyorini Sulistyorini; Yolanda Evelin Manalu; Istiono Istiono (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the financial performance of PT Astra International Tbk for the 2021-2025 period using financial ratio analysis covering liquidity, profitability, solvency, and activity. The research method used is descriptive quantitative with secondary data in the form of the company's annual financial reports acquired from the Indonesia Stock Exchange (IDX) and the company's official website. The analysis technique is carried out through financial ratio calculations and time series analysis to observe the company's performance development from year to year. The results show that PT Astra International Tbk has had quite good and stable financial performance throughout the study period. The liquidity ratio indicates that the company is able to meet its short-term obligations well. The profitability ratio showed a significant increase in 2022 following the economic recovery following the COVID-19 pandemic, although it experienced a slight decline in the following year. The solvency ratio indicates that the company's capital structure remains healthy with controlled debt usage. Furthermore, the activity ratio indicates that the company is quite effective in utilizing assets to generate sales. Overall, PT Astra International Tbk is able to maintain stable financial performance amidst national and global economic dynamics.